A comparison of human chorionic gonadotropin and luteinizing hormone releasing hormone on the induction of spermiation and amplexus in the American toad (Anaxyrus americanus) - Kouba Andrew J; delBarco-Trillo Javier; Vance Carrie K; Milam Callie; Carr Meghan (Reproductive Biology and Endocrinology, 2012)
Abstract Background Captive breeding programs for endangered amphibian species often utilize exogenous hormones for species that are difficult to breed. The purpose of our study was to compare the efficacy of two different hormones at various concentrations on sperm production, quantity and quality over time in order to optimize assisted breeding. Methods Male American toads (Anaxyrus americanus) were divided into three separate treatment groups, with animals in each group rotated through different concentrations of luteinizing hormone releasing hormone analog (LHRH; 0.1, 1.0, 4.0 and 32 micrograms/toad), human chorionic gonadotropin (hCG; 50, 100, 200, and 300 IU), or the control over 24 hours. We evaluated the number of males that respond by producing spermic urine, the sperm concentration, percent motility, and quality of forward progression. We also evaluated the effects of hCG and LHRH on reproductive behavior as assessed by amplexus. Data were analyzed using the Generalized Estimating Equations incorporating repeated measures over time and including the main effects of treatment and time, and the treatment by time interaction. Results The hormone hCG was significantly more effective at stimulating spermiation in male Anaxyrus americanus than LHRH and showed a dose-dependent response in the number of animals producing sperm. At the most effective hCG dose (300 IU), 100% of the male toads produced sperm, compared to only 35% for the best LHRH dose tested (4.0 micrograms). In addition to having a greater number of responders (P < 0.05), the 300 IU hCG treatment group had a much higher average sperm concentration (P < 0.05) than the treatment group receiving 4.0 micrograms LHRH. In contrast, these two treatments did not result in significant differences in sperm motility or quality of forward progressive motility. However, more males went into amplexus when treated with LHRH vs. hCG (90% vs. 75%) by nine hours post-administration. Conclusion There is a clear dichotomy between the two hormones’ physiological responses on gamete production and stimulation of amplexus. Understanding how these two hormones influence physiology and reproductive behaviors in amphibians will have direct bearing on establishing similar breeding protocols for endangered species.